Notice of Withdrawal - Need for Conservation and Relocate the Historical Building Sylhet, Bangladesh - Farukh, MA (Journal of Environmental Science and Natural Resources, 2015)
16th February 1015. Due to some unavoidable reasons the editional board is willing to declare that the article entitled Need for Conservation and Relocate the Historical Building Sylhet, Bangladesh - M. M. Rahman published on volume 7(1), 2014 with the pages 281-288 is withdrawn from the said issue. Therefore, after this declaration the authors will not have the privilege to use this article as an intellectual property quoting this journal. Managing Editor DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22253